KÖNYVAJÁNLÓ - Oravecz, Adrienn (Különleges Bánásmód - Interdiszciplináris folyóirat, 2017)
Az ajánlott könyv: Strzalkowski, Ralph (2013): Never, never quit My Conductive Education. Conductive Education. England: Press Birmingham